Intensification of the process of dosing bulk concentrated feeds by sieve hopper - Nanka, Alexander; Kharchenko, Sergei; Sementsov, Volodymyr I.; Sementsov, Vitaliy V.; Abduev, Magomed (Eastern-European Journal of Enterprise Technologies, 2019)
The study addresses the development and substantiation of parameters for the hopper that is installed in the technological process for producing concentrated bulk feeds. The structures of hoppers, the ways of improving productivity and the quality of their operation were analyzed and the prospects for the development of this direction were determined. The effectiveness of dosing was enhanced by the modernization of the sieve hopper with a rarefied discharge of dosed material due to the use of the openings in the form of a five-petal epicycloid. To determine the rational design and kinematic parameters of the modernized sieve hopper, mathematical modeling of the movement of bulk medium was carried out, conditions of the process were selected and final mathematical expressions were found. In addition to the parameters of the moving hopper in expressions and during the experiments, the properties of bulk feeds were explored. The ranges of variation in the sizes of the holes of the bottom and upper sieves were determined, the amplitude and frequency of their oscillations, which are the important parameters of the process of dosing bulk feed on the proposed hopper. The modeling results were proved by the conducted experimental research. The dependences of the performance of a sieve hopper on its design and kinematic parameters in its basic and upgraded versions were experimentally established. The adequacy of the developed modeling was proved by admissible discrepancy of the results with the experimental results. Using these dependences on the condition of maximum effectiveness of dosing, the ranges of variation in the performance of the upgraded hopper, which amounted to 0.75…2.6 t/h were determined. It was established that the use of sieves with activators enhances the performance of the hopper by 15...44.4 %. The adequacy of the developed mathematical modeling was proved by admissible discrepancy of the results and experiments, which did not exceed 5 %. The result of our research is the devised procedure for studying the sieve-type hoppers, which implies a possibility to explore the impact of shapes and sizes of openings on the effectiveness of dosing bulk feeds